ENERGY AND PROTEIN BALANCE OF NILE TILAPIA FED WITH MORINGA AND MULBERRY LEAVES - Astuti, Dewi Apri; Becker, Klaus; Ritcher, Nahid (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
The study was to evaluate energy and protein balance of diet that contain extracted moringa and mulberry leaf, as each 30% protein replacement for fish meal in nile tilapia diets. Three diets were control, prepared with fishmeal (C), diet 1 contained methanol extracted moringa (D-1) and diet 2 contained mulberry leaf (D-2). Fifteen nile tilapia were randomly kept in a 5 L capacity individual respiration chamber in which the oxygen consumption of each fish could be measured continuously. Prior to the experiment fish were measured standard metabolic rate (SMR), routine metabolic rate (RMR) and scope for spontaneous activity (SSA). Parameter measured were body weight, energy intake (GEI), energy expenditure (EE), energy metabolism (ME), energy retention (ER) and protein utilization. The data were subjected to analysis of variance and were continued using Duncan’s Test. The results showed the average values of SMR, RMR and SSA were 49, 67 and 105 mg.kg -0.8.h-1 , respectively. GEI for the control group was lower than the other groups, while final body weight in group D-1 was the highest. The ER (g) for group D-2 was the highest while value of Protein Efficiency Ratio and Protein Production Value in group D-1 were the highest. It was concluded that methanol extract of moringa are quite palatable and could replace 30% of protein fish meal in diets for nile tilapia. Key words: moringa, mulberry, standard metabolic rate, routine metabolic rate, scope for spontaneous activity